The Impact Of Dams on Agricultural Productivity In Indonesia - Sapto Langgeng Apriyanto; Widyono Soetjipto (UNIVED Press, 2025)
The construction of dams plays a crucial role in water resource management, including irrigation, energy, and consumption, and is believed to contribute to overall welfare improvement. Several previous studies have highlighted the positive impact of large dams on agricultural productivity, particularly in terms of irrigation efficiency. However, the distribution of these benefits among local communities remains unclear. Some studies suggest that residents living near dams often receive fewer benefits. This study aims to evaluate the impact of large and small dams on agricultural productivity, measured by the frequency of rice harvests at the household level, using data from the Indonesia Family Life Survey (IFLS) 2007 and 2014, as well as spatial data on dams in Indonesia. The findings indicate that the presence of large dams tends to be negatively associated with the frequency of rice harvests for households near the dams. Conversely, small dams exhibit a different trend, where their presence is associated with increased agricultural productivity. This study employs a unique approach by considering the distance of households from dam locations to provide more accurate predictions of changes in agricultural productivity in areas near large dams compared to those farther away.